An Investigation of Emotional Intelligence and Counselling Self-efficacy Among Counsellors-in-training - Mohd Azrin Mohd Nasir; Nor Atikah Mat Ali; Abdul Rashid Abdul Aziz; Suzila Ismail; Farah Nadia Mohd Faudzi (Institute of Advanced Engineering and Science (IAES) in collaboration with Intelektual Pustaka Media Utama (IPMU)., 2024)
Indexed by Scopus